2017
DOI: 10.4172/2168-9717.1000188
|View full text |Cite
|
Sign up to set email alerts
|

Self-Managed Cooperative Housing by Mutual-Assistance as Introduced in Central America between 2004 and 2016 the Attractiveness of the ‘FUCVAM’ Model of Uruguay

Abstract: Journal of Architectural Engineering Technology AbstractThis paper discusses the importance of cooperative housing through mutual assistance and collective ownership in Latin America. Cooperative housing is a form of self-managed house building, which is of great importance for a growing number of low-income households. It makes possible the access to appropriate housing for families with lowincomes, that don't have other possibilities.The mutual self-managed cooperative housing model of the Uruguayan federati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Nevertheless, home sharing has always been present in the history of this country, either due to cultural aspects or economic limitations ( Shlomo, 2002 ). Specifically regarding (formal) housing cooperatives, nine were identified (0.044% of the 2 million Honduran houses) located mainly in the southern zone of Honduras ( Bredenoord, 2017 ; Instituto Nacional de Estadística de Honduras, 2017 ). These Honduran cooperatives like the rest in Central America, are being influenced by the Uruguayan model of Self-Managed Cooperatives Housing by Mutual-Assistance ( Domínguez, 2017 ).…”
Section: Background Literaturementioning
confidence: 99%
“…Nevertheless, home sharing has always been present in the history of this country, either due to cultural aspects or economic limitations ( Shlomo, 2002 ). Specifically regarding (formal) housing cooperatives, nine were identified (0.044% of the 2 million Honduran houses) located mainly in the southern zone of Honduras ( Bredenoord, 2017 ; Instituto Nacional de Estadística de Honduras, 2017 ). These Honduran cooperatives like the rest in Central America, are being influenced by the Uruguayan model of Self-Managed Cooperatives Housing by Mutual-Assistance ( Domínguez, 2017 ).…”
Section: Background Literaturementioning
confidence: 99%
“…The cohousing model was created in Denmark in the early 1970s as an innovative form of collective housing and later spread to other northern European countries, the USA [18] and other latitudes such as Uruguay [19]. In recent years, cohousing has re-emerged in the USA, Europe, Australia, New Zealand and Japan [16,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Cooperative housing models require the active participation of the members in the construction and maintenance of buildings, as well as in the management of the housing cooperative itself. It was also found that most housing cooperatives accompany a CTC ('casa comunal' in Spanish) in their activities [22].…”
Section: Central America: Ctcs For Housing Cooperativesmentioning
confidence: 99%
“…Following this CTC model, another was built in the nearby housing cooperative Juntando Manos. We Effect, a Swedish NGO, and Foundation Juan XXIII, a Spanish NGO, provided loan aid to these housing cooperatives [22].…”
Section: Nicaraguamentioning
confidence: 99%
See 1 more Smart Citation